Dynamic Changes of Pulmonary Arterial Pressure and Ductus Arteriosus in Human Newborns From Birth to 72 Hours of Age. Issue 3 (January 2016) - Kang, Chunmiao; Zhao, Enfa; Zhou, Yinghua; Zhao, Huayun; Liu, Yunyao; Gao, Ningning; Huang, Xiaoxin; Liu, Baomin
Abstract : Abstract: Normal pulmonary artery pressure and pulmonary hypertension assessment of newborns is rarely reported. The aim of the study is to explore dynamic changes of pulmonary arterial pressure and ductus arteriosus in human newborns from birth to 72 h of age with echocardiography. A total of 76 cases of normal newborns were prospectively detected by echocardiography after birth of 2 h, 6 h, 12 h, 24 h, 48 h, and 72 h, respectively. Ductus arteriosus diameter, blood shunt direction, blood flow velocity, and pressure gradient were recorded. The brachial artery blood pressure were measured to estimate the pulmonary artery systolic pressure (PASP) and pulmonary artery diastolic pressure (PADP) using patent ductus arteriosus pressure gradient method. The mean pulmonary artery pressure (PAMP) were calculated by equation of PAMP = PADP + 1/3(PASP-PADP). (1) There were 76 cases of normal newborns. Among them, 29 cases (38%) ductus arteriosus closed within 24 h, 59 cases (78%) closed within 48 h, 72 cases (95%) closed within 72 h, and 4 cases (5%) ductus arteriosus not closed within 72 h. (2) The ductus arteriosus diameter of 2 h, 6 h, 12 h, 24 h, 48 h, and 72 h after birth was 4.60 ± 0.59 mm, 3.37 ± 0.59 mm, 2.47 ± 0.49 mm, 1.89 ± 0.41 mm, 1.61 ± 0.35 mm, and 1.20 ± 0.24 mm, respectively. Compared all of the ductus arteriosus diameter of the above time periods, there were statistically differences with P < 0.05, respectively. (3) The mean PASP in 2 h, 6 h, 12 h, 24 h, 48 h, 72 h after birth were 76.58 ± 7.28 mm Hg, 65.53 ± 9.25mm Hg, 52.51 ± 9.07 mm Hg, 43.83 ± 7.90 mm Hg, 38.07 ± 8.26 mm Hg, and 36 ± 6.48 mm Hg, respectively. The PADP of the above time period were 37.88 ± 5.56 mm Hg, 29.93 ± 7.91 mm Hg, 23.43 ± 7.37 mm Hg, 19.70 ± 8.51 mm Hg, 13.85 ± 5.58 mm Hg, 13.25 ± 6.18 mm Hg, respectively. The PAMP of the above time period were 63.41 ± 7.03 mm Hg, 51.78 ± 9.82 mm Hg, 40.94 ± 9.32 mm Hg, 34.39 ± 9.89 mm Hg, 26.23 ± 7.49 mm Hg, 25.25 ± 8.29 mm Hg, respectively. There were statistically differences with P < 0.05 between each time periods of PASP, PADP, and PAMP. (4) The upper 95% limit reference range of PASP of normal newborns of 72 h after birth were 39.97 mm Hg. (1) Normal newborns ductus arteriosus diameter gradually decreased after birth, and 95% of them spontaneous closed within 24 to 72 h. (2) Normal newborns pulmonary artery pressure showed a gradually decline after birth, the upper 95% limit reference range for PASP measured in normal newborns <72 h of age was 39.97 mm Hg. Therefore, the diagnostic criteria of newborns pulmonary hypertension may be >40.00 mm Hg according to our limited study.